TNF receptor p55 mediates peripheral cytotoxic T cell deletion. - Speiser, D; Sebzda, E; Ohteki, T; Bachmann, M; Mak, T; Ohashi, P (1996)
Antigen driven lymphocyte expansion is limited by cell death in peripheral lymphoid tissues avoiding overwhelming immune responses and autoimmunity. Signals associated with ligation of Fas can lead to lymphocyte apoptosis, but further, Fas-independent mechanisms have been postulated. Recent in vitro experiments demonstrated a role for tumor necrosis factor (TNF). In mice transgenic for the T cell receptor (TCR) specific for H-2Dand and the lymphocytic choriomeningitis virus (LCMV) glycoprotein aa 33-41 (GP33) we injected the peptide GP33 in BSS i.v. After nine days, the majority of CTLs were deleted in mice with a functional TNF receptor p55. In contrast, TNF receptor p55 deficient mice showed continued expansion of activated cytotoxic T cells (CTL) in spleen, lymph nodes and liver. The peripheral T cells reached three times the normal numbers nine days after immunization, then they stopped to proliferate and could not be restimulated with antigen in vitro. Thus, the prolonged lymphocyte survival was associated with functional anergy. The data demonstrate a role for TNF receptor p55 in peripheral T cell deletion and suggests that the cytotoxic activity of TNF may help to control immune responses.